Biochar production with sugarcane straw (Saccharum sp.) (Research, Society and Development, 2022)
In the mechanized harvesting of sugarcane, thick layers of straw are deposited on the ground, hindering the regrowth and emergence of Saccharum sp. It is necessary to seek alternatives for its surplus, which can be used to produce biochar, material rich in carbon and which work as a soil conditioner and as a CO2 scavenger in the atmosphere. The aim was to produce biochar using sugarcane straw residues, analyzing the best conditions for production and performance. Pyrolysis was carried out in a muffle oven for the treatments: T1: 200 °C, T2: 250 °C, T3: 300 °C and T4: 350 °C, residence time 2 hours. The proximate analysis of the biochar was carried out, with the determination of volatile matter, ash, fixed carbon and gravimetric yield. Through Scanning Electron Microscopy (SEM) the morphological structures of the material were identified and with the Thermogravimetric Analysis the mechanisms of thermal degradation were determined. The results were 23.51% (T1) and 63.74% (T4) for fixed carbon and 85.01% (T1) and 28.11% (T4) for the gravimetric yield of biochar. From the SEM it was observed a greater presence of pores in the biochar T2 and T3. Treatment T2 had the best balance between fixed carbon content and gravimetric yield, while the T3 showed greater thermal stability. It is concluded that the temperature range that presents the best conditions for production and performance of biochar is between 250 °C and 300 °C.